2020
DOI: 10.1097/bsd.0000000000000999
|View full text |Cite
|
Sign up to set email alerts
|

Two Doses of Tranexamic Acid Reduce Blood Loss in Primary Posterior Lumbar Fusion Surgery

Abstract: Purpose: Tranexamic acid (TXA) has been widely used in hip and knee arthroplasty to reduce perioperative blood loss and blood transfusion, but the dosage and efficacy of TXA in posterior lumbar spinal surgery are not fully clear. The aim of this study was to investigate the efficacy and safety of TXA and to determine whether 2 doses of TXA could reduce the blood loss in primary single-segment or double-segment posterior lumbar fusion surgery. Materials and Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Tranexamic acid, a frequently used haemostatic drug in orthopedic surgery, has been widely employed in spinal surgery to reduce intraoperative bleeding and hidden blood loss with the absence of thrombo-embolic events [ 27 , 28 ]. The current study focuses on the use of tranexamic acid in posterior spinal fusion, mainly by intravenous drip and topical application; Zhinan Ren [ 29 ] applied a topical tranexamic acid dip (1 g tranexamic acid in 100 mL saline solution) for 5 minutes before wound closure and showed a significant reduction in postoperative invisible blood loss, similar to the findings of Shi [ 30 ] et al On the other hand, Zhu [ 31 ] advocated one intravenous dose of tranexamic acid 30 min before surgery and one dose 3 h after the start of surgery, while Zheng [ 32 ] suggested a combination of intravenous drip and topical application to reduce intraoperative bleeding. This study also showed that tranexamic acid does not increase the risk of thrombosis and does not have a serious impact on the patient’s liver or kidney function.…”
Section: Discussionmentioning
confidence: 53%
“…Tranexamic acid, a frequently used haemostatic drug in orthopedic surgery, has been widely employed in spinal surgery to reduce intraoperative bleeding and hidden blood loss with the absence of thrombo-embolic events [ 27 , 28 ]. The current study focuses on the use of tranexamic acid in posterior spinal fusion, mainly by intravenous drip and topical application; Zhinan Ren [ 29 ] applied a topical tranexamic acid dip (1 g tranexamic acid in 100 mL saline solution) for 5 minutes before wound closure and showed a significant reduction in postoperative invisible blood loss, similar to the findings of Shi [ 30 ] et al On the other hand, Zhu [ 31 ] advocated one intravenous dose of tranexamic acid 30 min before surgery and one dose 3 h after the start of surgery, while Zheng [ 32 ] suggested a combination of intravenous drip and topical application to reduce intraoperative bleeding. This study also showed that tranexamic acid does not increase the risk of thrombosis and does not have a serious impact on the patient’s liver or kidney function.…”
Section: Discussionmentioning
confidence: 53%
“…Thirteen trials with 1,213 participants were eligible for inclusion in the metaanalysis [13][14][15][16][17][18][19][20][21][22][23][24][25] (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…[15] The action mechanism of TXA and EACA is similar as competes to saturate the lysine binding site of plasminogen. [16] The fibrinolysis inhibitor AP inactivates free plasmin to inhibit fibrinolysis. Several studies and meta-analyses have identified antifibrinolytics as an effective method of hemostasis during spinal surgery.…”
Section: Introductionmentioning
confidence: 99%